2003
DOI: 10.1002/jclp.10130
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the effectiveness of bibliotherapy for alcohol problems

Abstract: and the investigation of relational factors. In meta-analyses some variation will always exist, whether due to chance or to differences in trial context or content [5,6]. On its own, variance in a meta-analysis does not de-legitimize that meta-analysis, nor does it necessarily mask key causes of variation. Indeed, once these relational factors are specified , measured and tested in the same way in which specific factors are currently dealt with, meta-analyses of the trials of these new tests would still be sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(104 citation statements)
references
References 39 publications
6
91
0
7
Order By: Relevance
“…However, these findings differ from FRESH START in that they found no differences in weight loss by accrual source. Indeed, our study may be similar to a meta-analysis by Apodaca and Miller, who found that self-help bibliotherapy was less effective among drinkers who were identified through at risk screening than those who were self-referred (12 *P values reflect the difference between recruitment sources within each treatment arm. cIntervention arm, self-referred (n = 98) and registry (n = 155).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…However, these findings differ from FRESH START in that they found no differences in weight loss by accrual source. Indeed, our study may be similar to a meta-analysis by Apodaca and Miller, who found that self-help bibliotherapy was less effective among drinkers who were identified through at risk screening than those who were self-referred (12 *P values reflect the difference between recruitment sources within each treatment arm. cIntervention arm, self-referred (n = 98) and registry (n = 155).…”
Section: Discussionsupporting
confidence: 79%
“…Servings per day of fruits and vegetables and percent energy from fat (total and saturated) were derived using the Diet History Questionnaire (16). Additionally, at baseline, the following additional measures were collected: sociodemographic characteristics (treatment, education, and income); cancer coping style (modified Mini-Mental Adjustment to Cancer subscale); barriers to exercise and eating a low-fat, high fruit and vegetable diet; quality-of-life (Functional Assessment of Cancer Therapy); risk for depression (Center for Epidemiologic Studies of Depression); social support (Duke Social Support Index); comorbidity; perceived health; self-efficacy and stage of readiness for exercising z150 min/wk, eating five or more servings of fruits and vegetables per day and consuming a low-fat diet; smoking; and weight status (12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Apodaca & Miller reviewed the value of self-help literature, which is often used as part of a brief alcohol intervention, in a meta-analysis. 36 These authors found that self-help materials can reduce the alcohol consumption of patients without a one-on-one consultation. Moreover, this intervention is cost-effective, given the large number of risky drinkers.…”
Section: Signor Et Almentioning
confidence: 99%
“…Un programme d'autotraitement, à l'aide d'un manuel ou d'un site Internet, a déjà fait ses preuves pour diminuer ou cesser la consommation d'alcool (Apodaca & Miller, 2003 ;Marlatt et al, 1998). Notamment, le programme Alcochoix+, créé au Québec (Simoneau, Landry & Tremblay, 2004), est reconnu comme apportant des gains thérapeutiques aux personnes souhaitant réduire ou cesser leur consommation d'alcool.…”
Section: Introductionunclassified